Improving Patient Health Literacy in Hospitals – A Challenge for Hospital Health Education Programs - Wang MJ; Lo YT (Dove Medical Press, 2021)
Ming-Jye Wang,1,2 Yi-Ting Lo3 1Department of Secretariat, National Taiwan University Hospital Hsin-Chu Branch, Hsinchu, Taiwan; 2Department of Healthcare Management, Yuanpei University of Medical Technology, Hsinchu, Taiwan; 3Department of Development and Planning, National Taiwan University Hospital Hsin-Chu Branch, Hsinchu, TaiwanCorrespondence: Ming-Jye WangDepartment of Secretariat, National Taiwan University Hospital Hsin-Chu Branch, No. 25, Lane 442, Sec.1, Jingguo Road, Hsinchu, 300, TaiwanTel +886 3 5326151 Ext. 8897Fax +886 3 5329157Email jye9129@gmail.comBackground: The health literacy of hospital patients has become a very important issue, especially in the face of emerging infectious diseases. The design of and measures used by hospitals, however, have not yet taken into account whether patients can develop their health literacy through the process of medical treatment. Hospitals should take on this role as part of health education programs.Methods: A cross-sectional survey was conducted at pre-admission testing center patients waiting to be hospitalized in a regional teaching hospital. A purposive sampling method was used to recruit 406 patients via self-administered questionnaires.Results: Among the 406 participants, 36.1% had adequate health literacy. There were significant differences in age, education attainment, and history of chronic diseases for health literacy. The ability to find and judge information on health was lower. Watching health-related TV programs was positively correlated with health literacy. Health literacy, health promotion literacy, and understanding information on health were positively correlated to self-care and management. 65.8% of patients did not understand the treatment for which they were being admitted. Health literacy, healthcare health literacy, the ability to judge health information were positively related to understanding the treatment.Conclusion: Health literacy is a critical facilitating factor in improving self-care and management and understanding treatment on admission. Health education programs cannot, however, be one-size-fits-all. To help patients change their behavior, the change must be made easy. To this end, health information in the form of entertainment programs and simplified materials may be useful and even necessary.Keywords: health literacy, health information, health promotion, infectious diseases, medical treatment, hospitals